The addition of whey protein to a carbohydrate-electrolyte drink does not influence post-exercise rehydration - Hobson, R.; James, L. (Journal of Sports Sciences, 2015)
The addition of whey protein to a carbohydrate-electrolyte drink has been shown to enhance post-exercise rehydration when a volume below that recommended for full fluid balance restoration is provided. We investigated if this held true when volumes sufficient to restore fluid balance were consumed and if differences might be explained by changes in plasma albumin content. Sixteen participants lost ~1.9% of their pre-exercise body mass by cycling in the heat and rehydrated with 150% of body mass lost with either a 60 g/L carbohydrate drink (CHO) or a 60 g/L carbohydrate, 20 g/L whey protein isolate drink (CHO-P). Urine and blood samples were collected pre-exercise, post-exercise, post-rehydration and every hour for 4 h post-rehydration. There was no difference between trials for total urine production (CHO 1057 ± 319 mL; CHO-P 970 ± 334 mL; P = 0.209), drink retention (CHO 51 ± 12%; CHO-P 55 ± 15%; P = 0.195) or net fluid balance (CHO -393 ± 272 mL; CHO-P -307 ± 331 mL; P = 0.284). Plasma albumin content relative to pre-exercise was increased from 2 to 4 h during CHO-P only. These results demonstrate that the addition of whey protein isolate to a carbohydrate-electrolyte drink neither enhances nor inhibits rehydration. Therefore, where post-exercise protein ingestion might benefit recovery, this can be consumed without effecting rehydration.